The Relationship of School Principal Supervision and Teacher Work Motivation with Teacher Job Satisfaction - Shilvya Nanulaitta; Nelma Liklikwatil (Indonesian Journal of Global Health Research, 2022)
High motivation and satisfaction will contribute to a person's performance at work. In this case, its achievement requires support from all parties. Supervision is one way to see, review and assess employee performance by superiors. This research aimed to determine the relationship between principal supervision and teacher motivation and satisfaction at SD Gugus Sunglassess Nusaniwe. The population in this study were all teachers, totaling 146 samples. The sampling technique was determined using proportional random sampling. So we got 109 samples. The instrument used in this research was a questionnaire using 5 answer choices. The instrument has been tested for validity and reliability with a significance level of 0.361 > r table. The reliability test uses the Cronbach's alpha formula > 0.7. Analysis uses multiple correlation analysis methods. The results of the research show that there is a positive and significant relationship between principal supervision and teacher satisfaction at SD Gugus I Sunglasses Nusaniwe Ambon Tcount value (7.064) t-table (1.982) and there is a positive and significant relationship between principal supervision and teacher work motivation with elementary school teacher satisfaction Fcount (40.896) > Ftable (0.660).